Women and emancipatory politics in the former Lebowa bantustan of South Africa, 1940s to present - Bruchhausen, Sarah Lynn (University of the Witwatersrand, Johannesburg, 2024)
This thesis provides a gendered and subaltern historical perspective of women’s emancipatory politics in the former Lebowa bantustan of South Africa from the late-colonial period of segregation (1940s) to the post-apartheid present (2022). It begins with an examination of the popular uprisings during the period of the 1940s to the early-1960s in which black women championed radical insurgent struggles against colonial-cum-apartheid processes of land dispossession, enclosure of the commons, excessive taxation, and the criminalisation of women’s subsistence lifestyles. Attention then shifts to the intensely repressive period in the aftermath of these rural uprisings and the making of the Lebowa bantustan during the 1960s and 1970s. In this period, women’s emancipatory praxes were drastically constrained and their political resistance took on more diffused and less organised forms. A popular expression of emancipatory politics during this period was the creation of different local women-made grassroots organisations engaged in collective praxes of care- giving, mutual aid, and community development, aimed at creating life-affirming projects and dignified ways of living, under harsh socio-spatial and political constraints. These rural women’s grassroots organisations developed in response to the growing crisis of social reproduction in Lebowa’s villages during the 1970s and were eclipsed by more militant modes of resistance in the insurrectionary climate of the 1980s. A younger generation of women, involved as comrades in the youth and labour movements, came to the fore as protagonists of the popular struggle for freedom in Lebowa, and engaged in certain aspects of the longer history of black women’s struggles for self-determination and rights to the commons in rural South Africa. Lastly, this thesis considers the 1994 transition to democracy and the subsequent post-apartheid era in today’s Limpopo Province. Using the Makotse Women’s Club as a case study, it argues that grassroots women’s organisations presently engaged in the praxis of a radical politics of care in villages of the former Lebowa bantustan are the most recent expression of an emancipatory mode of politics in rural South Africa with a long and rich history that stretches back to the radical uprisings of the mid-twentieth century. Overall, the history presented in this thesis suggests that the creation of autonomous spaces of the common and the defence of subsistence lifestyles has been, and continues to be, a defining characteristic of rural women’s emancipatory politics in the former bantustans of South Africa.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, In the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Rural resistance; emancipatory politics; women; Lebowa Bantustan; social history; SDG-5: Gender equality